IMPLEMENTASI METODE AHP DALAM SISTEM PENDUKUNG KEPUTUSAN UNTUK PENERIMAAN KARYAWAN DI SASHOP KOTA GORONTALO - Yunus, Yulanda; Maliki, Ona; Gani, Hilmansyah (Universitas Muhammadiyah Gorontalo, 2025)
The development of technology and business competition encourages companies to improve performance, including the employee selection process. This study designs a Decision Support System (DSS) for employee recruitment at Sashop Kota Gorontalo to accelerate selection and minimize assessment errors. The system assists decision-makers in selecting candidates more objectively based on predetermined criteria. Additionally, structured data storage makes administrative processes more efficient compared to manual methods. The system is developed using the Analytic Hierarchy Process (AHP) method with PHP, HTML, and MySQL and is modeled using UML. White-box and black-box testing show that the system functions as designed, with a region value (R) = 2, independent paths = 2, and cyclomatic complexity (CC) = 2.